A trace of memory - Laumer, Keith, 1925-1993; Birmingham, Lloyd, 1924-2010 (Salt Lake City, UT : Project Gutenberg, 2023)
"A Trace of Memory" by Keith Laumer is a science fiction novel written in the early 1960s. The story revolves around Legion, a soldier of fortune who unexpectedly finds himself on a mysterious and dangerous journey across time and space, involving elements of memory and identity. With the backdrop of espionage and adventure, the narrative explores themes of amnesia and the pursuit of one's past. The opening of the novel introduces Legion as he wakes up in a strange, blood-stained environment aboard a deserted spacecraft, where he discovers the dead bodies of his friends and associates. The narrative quickly escalates as he learns he is being hunted by "Hunters," mysterious entities that track down criminals. As he attempts to escape with a wounded friend, the story shifts to present-day where Legion is initially characterized as a down-and-out figure contemplating petty crime, eventually leading to an encounter with a mysterious Mr. Foster. This interaction sets the stage for a deeper exploration of their identities and how their intertwined fates will unfold against the backdrop of cosmic danger and the search for truth. (This is an automatically generated summary.)
Release date is 2023-11-03
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Extraterrestrial beings -- Fiction; Space ships -- Fiction; Memory -- Fiction; Stonehenge (England) -- Fiction